Recycling of Date-Palm Fiber to Produce Pleurotus Cornucopiae Var. Citrinopileatus Mushroom - Owaid, Mustafa Nadhim; Saleem Al-Saeedi, Sajid Salahuddin; Abed, Idham Ali (International Journal of Environment, 2017)
In this study, some local available organic matters, which are including wheat straw (Triticum aestivum), sawdust, and fiber of date palm (Phoenix dactylifera L.), were used for growing and cultivating of bright yellow oyster mushroom Pleurotus cornucopiae var. citrinopileatus. The possibility of using date palm fiber (in mixtures with other organic residues) as a substrate for the cultivation and production of fruiting bodies of P. cornucopiae var. citrinopileatus was investigated. This mushroom is capable of biorecycling and utilization of some mixtures of lignocellulosic substrates successfully, especially the mixture S3 (50% wheat straw, 30% sawdust, and 20% date palm fiber). The lower mycelia completion time was 17 days, that shown in bags of the S3 substrate. Date-palm fiber substrate exhibited best growth intensity level (moderate) significantly (p